A Comprehensive Analysis of Narrative and Character Elements in The Conjuring (2013) Through Repertoire of Elements and Propp’s Theory - Indradewi, Amalia; Jayantini, I Gusti Agung Sri Rwa (Journal of Language and Literature Studies, 2024)
This study provides a comprehensive analysis of the 2013’s movie The Conjuring through Nick Lacey’s Repertoire of Elements and Vladimir Propp’s Narrative Theory. The movie, directed by James Wan, is recognized for its intricate horror narrative and rich character development. By examining the movie’s use of style, iconography, character roles, narrative structure, and setting, this research demonstrated how these elements worked together to create a compelling supernatural experience. Applying Lacey’s theory revealed the movie’s adherence to genre conventions through its dark, atmospheric settings and minimal lighting. Interestingly, the movie did not feature a "false hero", a deviation from Propp’s theory, which the movie emphasized the clear moral presented in the story. The absence of this character type suggested a more straightforward narrative focus on the struggle between good and evil, without the complication of betrayal from the protagonist’s ranks. In conclusion, The Conjuring Movie’s linguistic and visual elements were integral to the movie’s ability to engage and terrify its audience. The camera work, lighting, and sound, combined with a well-defined character structure, created a compelling narrative that resonated with viewers, reinforcing the movie’s status in the supernatural horror genre.